15.8k views
0 votes
Which expression is equivalent to 3(x - y) + y? 3x - 4y 3x - 3y 3x - 2y 3(x - 2y)

User Lazos
by
5.2k points

2 Answers

4 votes

9514 1404 393

Answer:

(c) 3x - 2y

Explanation:

Use the distributive property to eliminate parentheses, then collect terms.

3(x -y) +y = 3x -3y +y = 3x +(-3+1)y = 3x -2y

User Steve Summit
by
6.4k points
3 votes

Now we have to find,

The expression which is equivalent to,

→ 3(x - y) + y

Let's get the solution,

→ 3(x - y) + y

→ 3x - 3y + y

→ 3x - 2y

Hence, required expression is 3x - 2y.

User Nakwa
by
5.0k points